Kepemimpinan Kepala Sekolah Perempuan dalam Meningkatkan Budaya dan Mutu Pendidikan - Zahra Rafia Rani Siregar; Muthi' Nur Hanifah; Zaimiri Zaimiri; Solihah Titin Sumanti; Zaini Dahlan (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study aims to describe the leadership of a female principal in improving school culture and educational quality at MTs Swasta Hasanuddin Medan. The study employed a qualitative approach using a field research design. Data were collected through observation, interviews, and documentation, and were analyzed descriptively to obtain a comprehensive understanding of the phenomenon under investigation. The findings indicate that the female principal plays a significant role in developing a positive school culture through exemplary leadership, effective communication, discipline, a humanistic approach, and collaboration with all members of the school community. Her leadership also contributes to improving educational quality by developing tahsin and tahfiz programs, supporting arts and sports activities, enhancing teachers’ professionalism, and creating a conducive learning environment. Although she faces challenges related to gender stereotypes and social perceptions of female leadership, she demonstrates competence, responsibility, and innovation in carrying out her duties. Therefore, the leadership of the female principal has made a positive contribution to fostering a harmonious school culture and continuously improving the quality of education. This study is expected to serve as a reference for educational institutions in developing professional, inclusive, and quality-oriented leadership.